The investigation of the characteristics of spatial filters - I. M. Pershin (Современная наука и инновации, 2024)
The paper presents the results of studies of spatial filters used to extract useful information from distributed signals subject to significant noise influences. The adjustment of the spatial filter to the selection of a given spatial mode is shown, and the results of modeling the operation of the considered spatial filter are also presented.